Analisis layanan e-resources selama pembelajaran daring di UPT Perpustakaan UIN Sayyid Ali Rahmatullah Tulungagung - Samsul Huda (IJAL (Indonesian Journal of Academic Librarianship), 2022)
The study aimed to evaluate the use of electronic collections by students at the UIN SATU Tulungagung Library. This research uses a qualitative method with a descriptive approach—data collection techniques through observation, interviews, and documentation. The results showed that the use of electronic collections by UIN SATU Tulungagung students still needed to be improved. Increasing this utilization can be done by providing electronic collections under the needs of study programs and more intensive user education activities.